(untitled) - Taket, A. R. (New York, 2000)
The past two decades have seen an increase in the number of organisations working together in multiagency settings and increased calls for partnership and participation in organisational and public life. Models for this kind of working arrangement range from contracting out and joint planning, through to more formal arrangements such as setting up a joint agency. How to make these arrangements effective in developing policy and aiding decision-making can, however, be problematic. To make the multiagency setting work, organisations must manage diversity, resolve conflict and promote collaboration. The processes for effective decision-making in multiagency settings form the central concern of this book. Group processes must become more participatory, democratic and empowering. Illustrated with case studies drawn from the US, Africa, Asia, Latin America, as well as the UK and Europe, the book surveys the range of multiagency settings, explores the mechanisms and processes for multiagency work, and reviews a range of processes and tools that have shown themselves to be effective. Partnership & Participation offers no guaranteed answers, but provides a useful framework and stimulating guidelines for those facing the many questions that are raised by working in a multiagency setting.
Keywords: Joint ventures,Decision making,Dự án liên doanh,Ra quyết định